Pemberian Berbagai Level Tepung Cangkang Udang Ke Dalam Ransum Anak Puyuh Dalam Masa Pertumbuhan (Umur 1–6 Minggu) - B. Bakrie; E. Manshur; I. M. Sukadana (Jurnal Penelitian Pertanian Terapan, 2012)
Have conducted a research on the use of shrimp shell powder (TCU) in cattle rations quail, with the aim to determine the level of use that are suitable for quail during growth from age 1 day to 6 weeks. The study was conducted using 200 one-day-old quail tail, with a Completely Randomized Design (CRD) consisting of 5 treatments and 4 replications. The treatments tested were of 5 types of rations, including: a) commercial feed without the addition of TCU (R0), b) commercial feed plus 5% TCU (R1), c) commercial feed plus 10% TCU (R2), d) commercial feed plus 15% TCU (R3), and e) of commercial feed plus 20% TCU (R4). Parameters measured and calculated during the observation are included: a) feed intake, b) body weight gain (UN), and c) feed conversion. The results indicate that the addition of TCU into the feed causes a decrease in feed intake and the UN, but improves feed conversion by livestock quail. TCU can be added up to level 10% in animal feed quail, but the best results obtained by giving just as much as 5%. Keywords: Shrimp Shells, Quail, feed comsumtion, feed convertion